MENUMBUHKAN SIKAP PERSATUAN MELALUI TRADISI LOPIS RAKSASA DI KOTA PEKALONGAN - Yusuf Rozin; Atiqa Sabardila (Universitas PGRI Adi Buana Surabaya, 2022)
This article has the following objectives: (1) the background of the giant lopis tradition, (2) when to implement the giant lopis tradition in the krapyak of Pekaongan City, (3) The attitude of unity through the giant lopis tradition in Pekalongan City. This study used a qualitative descriptive method, data collection was carried out by observation and regional archives through the official website of Pekalongan City. The results of this study indicate that the Lopis Giant